Pengaruh Dana Pihak Ketiga Dan Beban Operasional Pendapatan Operasioanal (BOPO) Terhadap Profitabilitas Pada Bank Umum Milik Negara Di Indonesia - Lazarus D. A. Luase; Petrus E. De Rozari; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to find out and explain the influence of Third Party Funds and Operating Income Operating Expenses (BOPO) on profitability in state-owned commercial banks in Indonesia. The type of research used by the researcher is quantitative research using primary data. The data analysis techniques used include, panel data regression analysis, classical assumption test and hypothesis test using the Eviews 9 analysis tool. The results of the T test showed that the third-party fund variable had an effect but not significantly on profitability and the Operating Income Operating Expense (Bopo) variable had a significant effect on profitability and the F test result showed that the third-party fund variable and Operating Income Operating Expense (Bopo) simultaneously had a significant effect on profitability.